2021
DOI: 10.1007/s11740-021-01034-6
|View full text |Cite
|
Sign up to set email alerts
|

A time series classification approach to non-destructive hardness testing using magnetic Barkhausen noise emission

Abstract: The process setup of manufacturing processes is generally knowledge-based and carried out once for a material batch. Industry experts observe fluctuations in product quality and tool life, albeit the process setup remains unchanged. These fluctuations are mainly attributed to fluctuations in material parameters. An in-situ detection of changes in material parameters would enable manufacturers to adapt process parameters like forces or lubrication before turbulences like unexpectedly high tool wear or degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Experiments with an adapted version of Li et al's model architecture were conducted with the aim to classify the hardness of specimen from a 16MnCr15 fine blanking steel based on MBN measurements. Figure 4 The reached validation accuracies are considerably lower than those of Unterberg et al (2021). However, it becomes possible to compare the neural network's decision logic to existing domain knowledge, by checking whether the prototypes are consistent with findings reported in the literature on MBN.…”
Section: Drive Shaftmentioning
confidence: 71%
See 2 more Smart Citations
“…Experiments with an adapted version of Li et al's model architecture were conducted with the aim to classify the hardness of specimen from a 16MnCr15 fine blanking steel based on MBN measurements. Figure 4 The reached validation accuracies are considerably lower than those of Unterberg et al (2021). However, it becomes possible to compare the neural network's decision logic to existing domain knowledge, by checking whether the prototypes are consistent with findings reported in the literature on MBN.…”
Section: Drive Shaftmentioning
confidence: 71%
“…These variations occur on batch level, but also along single sheet metal coils. For other sheet-metal processing manufacturing processes, research has already shown that deviations in product quality occur due to variations in material properties (Unterberg et al 2021). A fine blanking line was equipped with sensors to capture material, process, and quality data to allow for a data-driven modeling of dependencies between material state, process state, and the resulting product quality in the long term (Niemietz et al 2020).…”
Section: Fine Blankingmentioning
confidence: 99%
See 1 more Smart Citation